2023
DOI: 10.3390/plants12142602
|View full text |Cite
|
Sign up to set email alerts
|

Some Physiological Effects of Nanofertilizers on Wheat-Aphid Interactions

Abstract: The increasing use of nanofertilizers in modern agriculture and their impact on crop yield and pest management require further research. In this study, the effects of nano-Fe, -Zn, and -Cu (which are synthesized based on nanochelating technology), and urea (N) fertilizers on the antioxidant activities of wheat plants (cv. Chamran), and the wheat green aphid Schizaphis graminum (Rondani) are investigated. The authors observed the highest levels of phenolics in non-infested nano-Zn-treated plants (26% higher com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 122 publications
0
6
0
Order By: Relevance
“…Studies by Kafel et al [ 50 ] on the toxic effects of zinc and cadmium on Spodoptera exigua clearly showed that exposure of the insect to these elements significantly reduces its survival. In our previous investigation [ 19 ] on the impact of nano-Zn treatment on wheat plants and wheat green aphid, we discovered that the application of nano-Zn led to an increase in the phenol content within aphid-infested wheat plants. This rise in phenol levels can be interpreted as an inhibitory factor against S. graminum , the aphid in question.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies by Kafel et al [ 50 ] on the toxic effects of zinc and cadmium on Spodoptera exigua clearly showed that exposure of the insect to these elements significantly reduces its survival. In our previous investigation [ 19 ] on the impact of nano-Zn treatment on wheat plants and wheat green aphid, we discovered that the application of nano-Zn led to an increase in the phenol content within aphid-infested wheat plants. This rise in phenol levels can be interpreted as an inhibitory factor against S. graminum , the aphid in question.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes were nearly in line with our findings, which showed that in the case of aphids, the nano-Cu treatment led to the most TPRP and the least amount of reproduction in terms of element abundance. The results of our previous investigation [ 19 ] regarding the impact of nano-Cu treatment on wheat and S. graminum demonstrated that this treatment did not exhibit significant toxicity toward wheat, only moderately affecting its enzymatic and non-enzymatic antioxidant systems. Conversely, the aphid displayed notably elevated levels of peroxidase (POX), CAT, and SOD enzymes, suggesting the pronounced toxicity of nano-Cu on the aphid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies revealed that plants or other organisms (e.g., animals, bacteria, Fungi, etc.) produce special components with inhibitory effects on pests [1][2][3]. Thanks to minimum or no harmful effects to the ecosystem, as well as their natural structures and sources, they have gained great attention.…”
Section: Introductionmentioning
confidence: 99%